Effects of Colombia's Social Protection System on Workers' Choice between Formal and Informal Employment - Camacho, Adriana (World Bank, Washington, DC, 2013)
This paper examines whether the Colombian government's expansion of social programs in the early 1990s, particularly the publicly provided health insurance, discouraged formal employment. Using household survey data and variation across municipalities in the onset of interviews for the SISBEN, the instrument used to identify beneficiaries for public health insurance, it shows robust and consistent estimates of an increase in informal employment of approximately 4 percentage points. Similar results are obtained using an alternative dataset, consisting of a panel of individuals interviewed for the first and second SISBEN. The findings suggest that marginal individuals optimized when deciding whether to participate in the formal sector.